1988
DOI: 10.1128/mcb.8.7.2964-2975.1988
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the HIS4 Translational Initiator Region in Saccharomyces cerevisiae

Abstract: We have mutated various features of the 5' noncoding region of the HIS4 mRNA in light of established Saccharomyces cerevisiae and mammalian consensus translational initiator regions. Our analysis indicates that insertion mutations that introduce G + C-rich sequences in the leader, particularly those that result in stable stem-loop structures in the 5' noncoding region of the HIS4 message, severely affect translation initiation. Mutations that alter the length of the HIS4 leader from 115 to 39 nucleotides had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This sequence, GAATTCCCATCTTGGGAATTC, is expected to form a stem-loop structure in the mRNA consisting of 8 bp (involving the underlined nucleotides) and five unpaired residues forming a loop (8). Sequences with potential secondary structures of similar predicted stabilities greatly inhibited translation of other yeast mRNAs (HIS4 and CYCJ) when introduced into the middle of the leader or just upstream from the AUG codon (1,2,6). Therefore, insertions of this sequence at any position in the GCN4 mRNA leader should inhibit GCN4 expression if initiation complexes must traverse the entire 591-nt leader to reach the GCN4 start codon.…”
Section: Resultsmentioning
confidence: 99%
“…This sequence, GAATTCCCATCTTGGGAATTC, is expected to form a stem-loop structure in the mRNA consisting of 8 bp (involving the underlined nucleotides) and five unpaired residues forming a loop (8). Sequences with potential secondary structures of similar predicted stabilities greatly inhibited translation of other yeast mRNAs (HIS4 and CYCJ) when introduced into the middle of the leader or just upstream from the AUG codon (1,2,6). Therefore, insertions of this sequence at any position in the GCN4 mRNA leader should inhibit GCN4 expression if initiation complexes must traverse the entire 591-nt leader to reach the GCN4 start codon.…”
Section: Resultsmentioning
confidence: 99%
“…As such, sequence elements within 5' TLs are important contributors to initiation efficiency and gene expression. Previous work demonstrated that features such as upstream open reading frames (uORFs), mRNA structures, and mRNA binding protein motifs influence the identification of the main start codon by the PIC (1)(2)(3)(4)(5)(6). These features have been studied largely independently, such that their relative importance in regulating gene expression from native 5' TLs has not been systematically evaluated in vivo.…”
Section: Introductionmentioning
confidence: 99%